Water Resources Assessment for Raw Water Purposes in Serang Watershed, Kulonprogro - Anik Sarminingsih (Jurnal Presipitasi, 2023)
One source of raw water for drinking water is river water. The raw water source for drinking water must meet the requirements for quantity, continuity, and quality. Raw water for drinking water must meet class I water quality requirements. This study aims to assess of the potential for water availability and water quality in the Serang River. Analysis of water availability used statistical methods and simulated rainfall-runoff with the HEC-HMS model. Calibration of the hydrological model was carried out in sub-watersheds where there were observational discharge data. Water availability is reviewed in the second-order river. Water quality status was analyzed using the Pollutant Index and Storet methods. The results of the analysis of water availability for reliable discharge with a probability of 80%, 90%, and 95% in several sections of the Serang River to order 2 rivers can be presented in the form of a flow duration curve. The results of the analysis of the status of water quality in several sections of the upstream Serang river based on the Storet method and the Polluter Index method show that in general, it is in a slightly polluted condition.